Polybrominated diphenyl ethers in foods from the Region of Valencia: Dietary exposure and risk assessment. (July 2020) - Pardo, Olga; Fernández, Sandra F.; Quijano, Leyre; Marín, Silvia; Villalba, Pilar; Corpas-Burgos, Francisca; Yusà, Vicent
Abstract: Dietary exposure to polybrominated diphenyl ethers (PBDEs) of the population in the Region of Valencia, Spain, was assessed. A group of 320 composite samples of different fatty foods was collected and analyzed, including the following: vegetable oils, and foods of animal origin such as (a) fish and seafood, (b) eggs, (c) milk and dairy products, and (d) meat and meat products. Two scenarios were assumed for left-censored results: lower-bound (LB) and upper-bound (UB). Vegetable oils, and fish and seafood presented the highest content of PBDEs [mean values of 503 and 464 pg g −1 wet weight (ww) for total PBDEs, respectively, in the UB]. The dominating congeners were BDE47 in the food categories of fish and seafood, meat and meat products, and vegetable oils, and BDE99 in the categories of eggs, and milk and dairy products. The dietary exposure to PBDEs through consumption of the studied foods by the population in the Region of Valencia was estimated for adults (>15 years of age) and young people (6–15 years of age). Average intake levels (UB scenario) were 1.443 and 3.456 ng kg bw −1 day −1 for adults and young people, respectively. In a risk-assessment context, the margin of exposure (MOE) for congener BDE47, -99,  −153, and −209 (ranged: 30-3E6) indicate that the current dietary exposure to these substances does not pose a risk to human health. Highlights: PBDE intake in Spain including representative sampling and foods with limited data. Salty fish, common in Spain and with high values, was included for the first time. Derived MOEs from PBDEs dietary exposure do not indicate possible health risk.